Studying methodological techniques for solving stereometric problems for high school students - Bashirova, Анар; Erboluly, Аскат (Рroblems of engineering and professional education, 2024)
This article is a comprehensive review of methodological approaches used in teaching senior schoolchildren to solve stereometric problems. It examines the importance of in-depth teaching of spatial geometry in the school curriculum and examines the effectiveness of different methodologies in this context. The author, a second-year master's student, shares his experience of researching teaching strategies used in modern educational institutions. The article provides the reader with an extensive overview of the main methodological approaches and tools used to develop spatial thinking in older schoolchildren. It analyzes in detail various curricula, teaching aids and techniques, and also provides recommendations for choosing the most effective approaches to teaching stereometry. This article is intended for mathematics teachers, educators and anyone interested in improving methods of teaching stereometry in school. Its contents will be a useful resource for developing curriculum, enriching lessons, and maximizing the understanding of stereometry problems in older students.